Association between Hashimoto’s Thyroiditis and Thyroid Cancer in 64,628 Patients - Resende de Paiva, Christina; Grønhøj, Christian; Feldt-Rasmussen, Ulla; von Buchwald, Christian (Frontiers in Oncology, 2017)
Background The incidence of thyroid cancer (TC) is increasing although explanatory causes are lacking. A link between cancer and inflammation is well documented but unclear for autoimmune thyroid diseases and TC. We aimed to systematically review the association between Hashimoto’s thyroiditis (HT) and papillary, follicular, medullary, anaplastic thyroid carcinoma, and thyroid lymphoma (TL). Methods PubMed, OVID Medline, Google Scholar, and the Cochrane Library were searched from 1955 to 2016. The inclusion criteria were age >18 years, ≥20 cases of HT or TC. We collectively examined the incidence of HT in TC and of TC in HT. Results We identified 36 studies (64,628 subjects) published between 1955 and 2016 from 13 countries. We found a relative risk (RR) of HT among papillary thyroid cancer (PTC) of 2.36 [95% confidence intervals (CIs) 1.55–3.29, p < 0.001], an RR of PTC among HT of 1.40 (95% CI 1.07–1.85, p = 0.016), and an RR of TL among HT of 9.74 (95% CI 3.93–24.13, p < 0.001). Conclusion We report an association between HT and PTC and between HT and TL. No association was found between HT and follicular, medullary, or anaplastic thyroid cancer.